Hepatitis C virus–induced tumor‐initiating cancer stem–like cells activate stromal fibroblasts in a xenograft tumor model. Issue 6 (30th October 2017) - Sasaki, Reina; Devhare, Pradip; Ray, Ratna B.; Ray, Ranjit
Abstract : Hepatitis C virus (HCV) often causes persistent infection and is an increasingly important factor in the etiology of fibrosis/cirrhosis and hepatocellular carcinoma, although the mechanisms for the disease processes remain unclear. We have shown previously that HCV infection generates an epithelial–mesenchymal transition state and tumor‐initiating cancer stem–like cells in human hepatocytes. In this study, we investigated whether HCV‐induced tumor‐initiating cancer stem–like cells when implanted into mice activate stromal fibroblasts. A number of fibroblast activation markers, including matrix metalloproteinase 2, were significantly increased at the mRNA or protein level in the xenograft tumors, suggesting the presence of tumor‐associated fibroblasts. Fibroblast activation markers of murine origin were specifically increased in tumor, suggesting that fibroblasts migrate to form stroma. Next, we demonstrated that conditioned medium from HCV‐infected human hepatocytes activates fibrosis‐related markers in hepatic stellate cells. We further observed that these HCV‐infected hepatocytes express transforming growth factor beta, which activates stromal fibroblast markers. Subsequent analysis suggested that anti–transforming growth factor beta neutralizing antibody, when incubated with conditioned medium from HCV‐infected hepatocytes, inhibits fibrosis marker activation in primary human hepatic stellate cells. Conclusion: HCV‐infected hepatocytes induce local fibroblast activation by secretion of transforming growth factor beta, and a preneoplastic or tumor state of the hepatocytes influences the network for the tumor‐associated fibroblast environment. (Hepatology 2017;66:1766–1778)